Sheek Muhammad Arsyad Al-Banjari's Islamic Economic Thinking and Its Relevance to Contemporary Islamic Economic Thinking - Muhammad Sauqi; M. Fahmi al-Amruzi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the relevance of Sheikh Muhammad Arsyad al-Banjari's Islamic economic thought and contemporary Islamic economic thought. This type of research is descriptive qualitative library research with historical, sociological, anthropological, and legal approaches. The findings from this study are the thoughts of Sheikh Muhammad al-Banjari regarding contemporary Islamic economics, which is about zakat based on the social conditions of society at that time which was dominated by the poor. But he also in his ijtihad quoted the thoughts of the previous Shafi'iyyah scholars. The influence of Sheikh Muhammad Arsyad al-Banjari is a continuation and expansion of Middle Eastern influence. After his arrival, his influence on the study of fiqh grew wider with the compilation of fiqh works by later scholars and their descendants.